KARAKTER TENAGA KERJA YANG DIBUTUHKAN DUNIA INDUSTRI KONSTRUKSI DI KABUPATEN TANAH DATAR - 2028-2032, Ayu Maharani (CIVED, 2018)
Abstract—The research begins from the lack of work foce character needed the construction industry in Tanah Datar District. This research is a descriptive study with the number of population as many as 103 construction industries in Tanah Datar. Sample in This research is as much as 51 construction industry by using technique propotional random sampling. The data were collected using a questionnaire with scale Likert consisting of 4 choices of answers with positive and negative statements.The number of items in the questionnaire were 72 points. The results of this study indicate from 18 indicators of power characters work required by the construction industry, there are 6 indicators included on very high category of responsibility, honest, discipline, hard work, achievement and religious As for which included in the high category that is 12 indicators, which include the high category of social care, independent, creative environmental care, friendly / communicative,peace love, curiosity, peace love, the spirit of nationality, love the homeland, democratic, fond read , and tolerance. Keywords: Character of Labor, World of Construction Industry